Rheumatoid arthritis and excess mortality: down but not out. A primary care cohort study using data from Clinical Practice Research Datalink. (23rd February 2018) - Abhishek, Abhishek; Nakafero, Georgina; Kuo, Chang-Fu; Mallen, Christian; Zhang, Weiya; Grainge, Matthew J; Doherty, Michael
Abstract: Objectives: To examine temporal trends in all-cause and cause-specific mortality in RA. Methods: Data from the Clinical Practice Research Datalink were used. Incident RA cases and four age-, sex- and general practice–matched controls were identified from at-risk cohorts for each calendar year and followed-up for up to 5 years. Mortality rates and 95% CIs were computed. Cox proportional hazard ratios (HRs) were calculated to estimate associations and adjusted for covariates. The temporal trend in mortality was examined using the Joinpoint regression program. Data management and analysis were performed using Stata version 14. Results: A total of 21 622 cases with incident RA and 86 488 controls were included. The mortality rate of RA cases and controls was 26.90 (95% CI 25.87, 27.97) and 18.92 (18.48, 19.36)/1000 person-years, respectively. The mortality rate in RA cases did not change significantly between 1990 and 2004 but decreased by 7.7%/year between 2005 and 2009. However, the mortality rate in controls improved steadily by 2.2%/year between 1990 and 2009. RA was associated with a 32% excess risk of mortality in the entire cohort [adjusted HR 1.32 (95% CI 1.26, 1.38)], but this was only 15% in cases incident after 2006 [adjusted HR 1.15 (95% CI 1.03, 1.29)]. Similarly, the HR of death due to cardiovascular diseases decreased in cases incident in recent years. Conclusion: The mortality rate in RA cases incident after the year 2006 has declined significantly, with a trend towards a decline in death from cardiovascular diseases. This could be due to improved management of RA. However, even in cohorts from recent years, RA still associates with higher mortality rates.